NF-Y coassociates with FOS at promoters, enhancers, repetitive elements, and inactive chromatin regions, and is stereo-positioned with growth-controlling transcription factors - Fleming, Joseph D.; Pavesi, Giulio; Benatti, Paolo; Imbriano, Carol; Mantovani, Roberto; Struhl, Kevin (Genome Research, 2013)
NF-Y, a trimeric transcription factor (TF) composed of two histone-like subunits (NF-YB and NF-YC) and a sequence-specific subunit (NF-YA), binds to the CCAAT motif, a common promoter element. Genome-wide mapping reveals 5000–15,000 NF-Y binding sites depending on the cell type, with the NF-YA and NF-YB subunits binding asymmetrically with respect to the CCAAT motif. Despite being characterized as a proximal promoter TF, only 25% of NF-Y sites map to promoters. A comparable number of NF-Y sites are located at enhancers, many of which are tissue specific, and nearly half of the NF-Y sites are in select subclasses of HERV LTR repeats. Unlike most TFs, NF-Y can access its target DNA motif in inactive (nonmodified) or polycomb-repressed chromatin domains. Unexpectedly, NF-Y extensively colocalizes with FOS in all genomic contexts, and this often occurs in the absence of JUN and the AP-1 motif. NF-Y also coassociates with a select cluster of growth-controlling and oncogenic TFs, consistent with the abundance of CCAAT motifs in the promoters of genes overexpressed in cancer. Interestingly, NF-Y and several growth-controlling TFs bind in a stereo-specific manner, suggesting a mechanism for cooperative action at promoters and enhancers. Our results indicate that NF-Y is not merely a commonly used proximal promoter TF, but rather performs a more diverse set of biological functions, many of which are likely to involve coassociation with FOS.
10.1101/gr.148080.112